2018
DOI: 10.4103/ijps.ijps_9_18
|View full text |Cite
|
Sign up to set email alerts
|

Transverse cervical vascular pedicle: It's extended use as ‘second-line’ recipient vessels in thoracic and upper arm reconstructions in addition to head-and-neck reconstructions

Abstract: Background:Selection of recipient vessels is one of the key factors for a successful microvascular reconstruction. Non-availability of primary recipient vessels in the vicinity necessitates surgeon to approach a remote second-line vascular access. Transverse cervical vessels (TCV) have been described as second-line vascular access for head-and-neck reconstructions. Due to its location, their use can be extended to the proximal chest and upper arm reconstructions.Aim:The aim of the study is to analyse the relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our experience has shown that even caudal sternal defects can be adequately reconstructed using the STA as a recipient, provided adequate pedicel length and flap size. Our findings, thus, promote a further option for reconstruction of chest wall defects in patients that lack vessels in vicinity of the defect and add to recent studies that suggest the use of transverse cervical vessels in these cases 35 . In theory, further branches of the external carotid artery, such as the facial or lingual artery that are commonly used in head and neck reconstructions, 36 could also be considered as alternative recipients in certain cases.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Our experience has shown that even caudal sternal defects can be adequately reconstructed using the STA as a recipient, provided adequate pedicel length and flap size. Our findings, thus, promote a further option for reconstruction of chest wall defects in patients that lack vessels in vicinity of the defect and add to recent studies that suggest the use of transverse cervical vessels in these cases 35 . In theory, further branches of the external carotid artery, such as the facial or lingual artery that are commonly used in head and neck reconstructions, 36 could also be considered as alternative recipients in certain cases.…”
Section: Discussionsupporting
confidence: 53%
“…Our findings, thus, promote a further option for reconstruction of chest wall defects in patients that lack vessels in vicinity of the defect and add to recent studies that suggest the use of transverse cervical vessels in these cases. 35 In theory, further branches of the external carotid artery, such as the facial or lingual artery that are commonly used in head and neck reconstructions, 36 could also be considered as alternative recipients in certain cases. However, because these branches are located more cranially, compared with the STA, pedicle length can be an issue.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the TCA as an arterial flap can be spread to cover larger areas such as the anterior chest and clavicle [ 15 ]. Muppireddy et al described how the TCA is a safe vessel for arterial flaps because it can anastomose and is an easily dissectible artery due to its location [ 18 ]. Additionally, patients who undergo targeted radiation therapy or treatment for recurrent tumors of the head and neck are at increased risk of damage to the vessels of the neck, specifically the external carotid artery and its branches, therefore, utilization of the TCA is a safe option for reconstructive surgery [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature on the absence of the SSA and TCA is limited [ 5 ]. Knowledge of anatomical variations in the arterial supply of the neck and muscles of the back can reduce surgical error and intraoperative complications [ 15 18 ]. In this case report, we describe the unilateral absence of the SSA and TCA from the TCT, and branches from the DSA providing blood supply to the trapezius and supraspinatus muscle on a male donor body.…”
Section: Introductionmentioning
confidence: 99%